Communities awareness towards Community Oriented Policing (COP) development and implementation in Malaysia - Hassan, Mohammad Mujaheed; Abdullah, Aldrin (Valley International, 2018)
The concept of community oriented policing has emerged in Malaysia since 2007 as an increasingly important strategy for controlling and preventing crime, as well as for enhancing community safety. The concept has been endorsed in three phases. The first phase only involves Kuala Lumpur, Selangor, Penang, and Johor Police Contingents, while the second phase involves every police contingent at the state level in Malaysia, and lastly, followed by the third phase that involves every police contingent in every regional in every state in Malaysia. The Community Oriented Policing Strategy (COPS) is a partnership between the local residents and the police in charge of the district. COP is a belief that by working together the police and the community can accomplish what neither can accomplish alone. Thus, the spirit of community empowerment, smart ship, and interdependency between all stakeholders, including community, police, NGOs, and other interested parties are very much needed in this country through active and inactive. The purposes of this paper are; (a) to determine the importance of COP, (b) to evaluate the community awareness towards COP implementation in Malaysia.